Skip to content
Related Articles

Related Articles

Class 11 RD Sharma Solutions – Chapter 13 Complex Numbers – Exercise 13.3

Improve Article
Save Article
  • Last Updated : 21 Feb, 2021
Improve Article
Save Article

Question 1. Find the square root of the following complex numbers.

(i) – 5 + 12i

(ii) -7 – 24i

(iii) 1 – i

(iv) – 8 – 6i

(v) 8 – 15i

(vi) -11 - 60\sqrt-1

(vii) 1 + 4\sqrt3

(viii) 4i

(ix) -i

Solution:

If b > 0, \sqrt{a+ib}=\pm\left[\left(\frac{a+\sqrt{a^2+b^2}}{2}\right)^{\frac{1}{2}}+i\left(\frac{-a+\sqrt{a^2+b^2}}{2}\right)^{\frac{1}{2}}\right]

If b < 0, \sqrt{a+ib}=\pm\left[\left(\frac{a+\sqrt{a^2+b^2}}{2}\right)^{\frac{1}{2}}-i\left(\frac{-a+\sqrt{a^2+b^2}}{2}\right)^{\frac{1}{2}}\right]

(i) – 5 + 12i

Given:

– 5 + 12i

We know, Z = a + ib

So, \sqrt{a + ib} = \sqrt{-5+12i}

Here, b > 0

Let us simplify now,

\sqrt{-5+12i}=\pm\left[\left(\frac{-5+\sqrt{(-5)^2+12^2}}{2}\right)^{\frac{1}{2}}+i\left(\frac{5+\sqrt{(-5)^2+12^2}}{2}\right)^{\frac{1}{2}}\right]\ \ \ [Since\ b>0]\\ =\pm\left[\left(\frac{-5+\sqrt{25+144}}{2}\right)^{\frac{1}{2}}+i\left(\frac{5+\sqrt{25+144}}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{-5+\sqrt{169}}{2}\right)^{\frac{1}{2}}+i\left(\frac{5+\sqrt{169}}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{-5+13}{2}\right)^{\frac{1}{2}}+i\left(\frac{5+13}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{8}{2}\right)^{\frac{1}{2}}+i\left(\frac{18}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[4^{\frac{1}{2}}+i9^{\frac{1}{2}}\right]\\ =\pm[2+3i]

∴ Square root of (– 5 + 12i) is ±[2 + 3i]

(ii) -7 – 24i

Given:

-7 – 24i

We know, Z = -7 – 24i

So, \sqrt{a + ib} = \sqrt{-7 - 24i}

Here, b < 0

Let us simplify now,

\sqrt{-7-24i}=\pm\left[\left(\frac{-7+\sqrt{(-7)^2+(-24)^2}}{2}\right)^{\frac{1}{2}}-i\left(\frac{7+\sqrt{(-7)^2+(-24)^2}}{2}\right)^{\frac{1}{2}}\right]\ \ \ [Since\ b<0]\\ =\pm\left[\left(\frac{-7+\sqrt{49+576}}{2}\right)^{\frac{1}{2}}-i\left(\frac{7+\sqrt{49+576}}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{-7+\sqrt{625}}{2}\right)^{\frac{1}{2}}-i\left(\frac{7+\sqrt{625}}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{-7+25}{2}\right)^{\frac{1}{2}}-i\left(\frac{7+25}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{18}{2}\right)^{\frac{1}{2}}-i\left(\frac{32}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[9^{\frac{1}{2}}-i16^{\frac{1}{2}}\right]\\ =\pm[3-4i]

∴ Square root of (-7 – 24i) is ± [3 – 4i]

(iii) 1 – i

Given:

1 – i

We know, Z = (1 – i)

So, \sqrt{a + ib} = \sqrt{1 - i}

Here, b < 0

Let us simplify now,

\sqrt{1-i}=\pm\left[\left(\frac{1+\sqrt{(1)^2+(-1)^2}}{2}\right)^{\frac{1}{2}}-i\left(\frac{-1+\sqrt{(1)^2+(-1)^2}}{2}\right)^{\frac{1}{2}}\right]\ \ \ [Since\ b<0]\\ =\pm\left[\left(\frac{1+\sqrt{1+1}}{2}\right)^{\frac{1}{2}}-i\left(\frac{-1+\sqrt{1+1}}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{1+\sqrt{2}}{2}\right)^{\frac{1}{2}}-i\left(\frac{-1+\sqrt{2}}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\sqrt{\frac{\sqrt2+1}{2}}\right)-i\left(\sqrt{\frac{\sqrt2-1}{2}}\right)\right]

∴ Square root of (1 – i) is ± \pm\left[\left(\sqrt{\frac{\sqrt2+1}{2}}\right)-i\left(\sqrt{\frac{\sqrt2-1}{2}}\right)\right]

(iv) -8 -6i

Given:

-8 -6i

We know, Z = -8 -6i

So, \sqrt{a + ib}  = -8 -6i

Here, b < 0

Let us simplify now,

\sqrt{-8-6i}=\pm\left[\left(\frac{-8+\sqrt{(-8)^2+(-6)^2}}{2}\right)^{\frac{1}{2}}-i\left(\frac{8+\sqrt{(-8)^2+(-6)^2}}{2}\right)^{\frac{1}{2}}\right]\ \ \ [Since\ b<0]\\ =\pm\left[\left(\frac{-8+\sqrt{64+36}}{2}\right)^{\frac{1}{2}}-i\left(\frac{8+\sqrt{64+36}}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{-8+\sqrt{100}}{2}\right)^{\frac{1}{2}}-i\left(\frac{8+\sqrt{100}}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{-8+10}{2}\right)^{\frac{1}{2}}-i\left(\frac{8+10}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{2}{2}\right)^{\frac{1}{2}}-i\left(\frac{10}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[1^{\frac{1}{2}}-i9^{\frac{1}{2}}\right]\\ =\pm[1-3i]

∴ Square root of (-8 -6i) is ± [1 – 3i]

(v) 8 – 15i

Given:

8 – 15i

We know, Z = 8 – 15i

So, \sqrt{a + ib}   = 8 – 15i

Here, b < 0

Let us simplify now,

\sqrt{8-15i}=\pm\left[\left(\frac{8+\sqrt{(8)^2+(-15)^2}}{2}\right)^{\frac{1}{2}}-i\left(\frac{-8+\sqrt{(8)^2+(-15)^2}}{2}\right)^{\frac{1}{2}}\right]\ \ \ [Since\ b<0]\\ =\pm\left[\left(\frac{8+\sqrt{64+225}}{2}\right)^{\frac{1}{2}}-i\left(\frac{-8+\sqrt{64+225}}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{8+\sqrt{289}}{2}\right)^{\frac{1}{2}}-i\left(\frac{-8+\sqrt{289}}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{8+17}{2}\right)^{\frac{1}{2}}-i\left(\frac{-8+17}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{25}{2}\right)^{\frac{1}{2}}-i\left(\frac{9}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\frac{5}{\sqrt2}-\frac{13}{\sqrt2}\right]\\ =\pm\frac{1}{\sqrt2}(5-3i)

∴ Square root of (8 – 15i) is ± \frac{1}{\sqrt2}(5-3i)

(vi) -11 - 60\sqrt{-1}

Given:

-11 - 60\sqrt{-1}

We know, Z = -11 - 60\sqrt{-1}

So, \sqrt{a + ib} = -11 - 60\sqrt{-1}

= -11 – 60i

Here, b < 0

Let us simplify now,

\sqrt{-11-60i}=\pm\left[\left(\frac{-11+\sqrt{(-11)^2+(-60)^2}}{2}\right)^{\frac{1}{2}}-i\left(\frac{11+\sqrt{(-11)^2+(60)^2}}{2}\right)^{\frac{1}{2}}\right]\ \ \ [Since\ b<0]\\ =\pm\left[\left(\frac{-11+\sqrt{121+3600}}{2}\right)^{\frac{1}{2}}-i\left(\frac{11+\sqrt{121+3600}}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{-11+\sqrt{3721}}{2}\right)^{\frac{1}{2}}-i\left(\frac{11+\sqrt{3721}}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{-11+61}{2}\right)^{\frac{1}{2}}-i\left(\frac{11+61}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{50}{2}\right)^{\frac{1}{2}}-i\left(\frac{72}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[25^{\frac{1}{2}-i36^{\frac{1}{2}}}\right]\\ =\pm(5-6i)

∴ Square root of (-11 - 60\sqrt{-1} ) is ± (5 – 6i)

(vii) 1 + 4\sqrt{-3}

Given:

1 + 4\sqrt{-3}

We know, Z = 1 + 4\sqrt{-3}

So, \sqrt{a + ib} = 1 + 4\sqrt{-3}

= 1 + 4(\sqrt{3}) (\sqrt{-1})\\ = 1 + 4\sqrt{3i}

Here, b > 0

Let us simplify now,

\sqrt{1+4\sqrt3i}=\pm\left[\left(\frac{1+\sqrt{(1)^2+(4\sqrt3)^2}}{2}\right)^{\frac{1}{2}}+i\left(\frac{-1+\sqrt{1^2+(4\sqrt3)^2}}{2}\right)^{\frac{1}{2}}\right]\ \ \ [Since\ b>0]\\ =\pm\left[\left(\frac{1+\sqrt{1+48}}{2}\right)^{\frac{1}{2}}+i\left(\frac{-1+\sqrt{1+48}}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{1+\sqrt{49}}{2}\right)^{\frac{1}{2}}+i\left(\frac{-1+\sqrt{49}}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{1+7}{2}\right)^{\frac{1}{2}}+i\left(\frac{-1+7}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{8}{2}\right)^{\frac{1}{2}}+i\left(\frac{6}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[4^{\frac{1}{2}}+i3^{\frac{1}{2}}\right]\\ =\pm[2+\sqrt3i]

∴ Square root of (1 + 4\sqrt{-3})  is ± (2+\sqrt3i)

(viii) 4i

Given:

4i

We know, Z = 4i

So, \sqrt{a + ib}  = 4i

Here, b > 0

Let us simplify now,

\sqrt{4i}=\pm\left[\left(\frac{0+\sqrt{(0)^2+(4)^2}}{2}\right)^{\frac{1}{2}}+i\left(\frac{0+\sqrt{0^2+(4)^2}}{2}\right)^{\frac{1}{2}}\right]\ \ \ [Since\ b>0]\\ =\pm\left[\left(\frac{0+\sqrt{0+16}}{2}\right)^{\frac{1}{2}}+i\left(\frac{0+\sqrt{0+16}}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{0+\sqrt{16}}{2}\right)^{\frac{1}{2}}+i\left(\frac{0+\sqrt{16}}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{0+4}{2}\right)^{\frac{1}{2}}+i\left(\frac{0+4}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{4}{2}\right)^{\frac{1}{2}}+i\left(\frac{4}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[2^{\frac{1}{2}}+i2^{\frac{1}{2}}\right]\\ =\pm[\sqrt2+\sqrt2i]\\ =\pm\sqrt2(1+i)

∴ Square root of 4i is ± \sqrt{2 (1 + i)}

(ix) –i

Given:

-i

We know, Z = -i

So, \sqrt{(a + ib)}  = -i

Here, b < 0

Let us simplify now,

\sqrt{-i}=\pm\left[\left(\frac{0+\sqrt{0^2+(-1)^2}}{2}\right)^{\frac{1}{2}}-i\left(\frac{0+\sqrt{0^2+(-1)^2}}{2}\right)^{\frac{1}{2}}\right]\ \ \ [Since\ b<0]\\ =\pm\left[\left(\frac{0+\sqrt{0+1}}{2}\right)^{\frac{1}{2}}-i\left(\frac{0+\sqrt{0+1}}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{0+\sqrt{1}}{2}\right)^{\frac{1}{2}}-i\left(\frac{0+\sqrt{1}}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{0+1}{2}\right)^{\frac{1}{2}}-i\left(\frac{0+1}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\left(\frac{1}{2}\right)^{\frac{1}{2}}-i\left(\frac{1}{2}\right)^{\frac{1}{2}}\right]\\ =\pm\left[\frac{1}{\sqrt2}-\frac{i}{\sqrt2}\right]\\ =\pm\frac{1}{\sqrt2}(1-i)

∴ Square root of –i is ± \frac{1}{\sqrt2} (1 - i)


My Personal Notes arrow_drop_up
Related Articles

Start Your Coding Journey Now!